The Pt Dopant Effect on Physical Properties of Ba0.2La0.8Fe2As2 - GÜLER, ADİL; BOYRAZ, CİHAT (SPRINGER, 2017)
We briefly report the variation of resistivity and the extraordinary magnetic behavior of the samples Ba0.2La0.8Fe2As2 and Pt-doped Ba0.2La0.8Fe2-xPt (x) As-2 (x = 0, 0.05, 0.1, and 0.15) prepared by a solid-state reaction method. All samples crystallize with the ThCr2Si2-type structure. We have investigated in detail the superconducting state with magnetization measurements in the temperature range 5-170 K, up to a field of 20 Oe. Substitution of Pt for Fe element produced induced the superconductivity. The results of direct substitution of non-isoelectronic Pt for Fe were also studied for similar compositions at different dopant rates (Kamihara et al., J. Am. Chem. Soc., 130, 3296-3297, 2008). Based on magnetization measurement data, we observed the variation of superconducting critical temperature (T (c)) by increasing the Pt dopant from x = 0 to x = 0.1. The dopant rate of x = 0.15 is the limit point of decreasing superconductivity because of lattice shrinking, attributed to the change of T (c). This should be an indication of geometric factor (pressure effect) by Pt substitution for Fe atoms (Li et al. 2008).
Keywords: Pt dopant effect; Lattice shrinkage; Geometric factor; Meissner effect; Superconductivity